2016
DOI: 10.1051/0004-6361/201629113
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropies in the HI gas distribution toward 3C 196

Abstract: Context. The local Galactic Hi gas was found to contain cold neutral medium (CNM) filaments that are aligned with polarized dust emission. These filaments appear to be dominated by the magnetic field and in this case turbulence is expected to show distinct anisotropies. Aims. We use the Galactic Effelsberg-Bonn Hi Survey (EBHIS) to derive 2D turbulence spectra for the Hi distribution in direction to 3C 196 and two more comparison fields. Methods. Prior to Fourier transform we apply a rotational symmetric 50% T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
4
28
0
Order By: Relevance
“…Over scales larger than the damping scales, neutrals are strongly coupled with ions and magnetic fields, and thus the turbulence properties measured in neutrals can also reflect the properties of turbulent magnetic fields. As expected, in the diffuse magnetized ISM, the H I gas distribution exhibits turbulence anisotropy (e.g., Kalberla and Kerp 2016), and both the velocity gradient (González-Casanova and Lazarian 2017, Yuen and Lazarian 2017a, 2017b) and density structure (Clark et al 2015) of H I gas are found to well trace the magnetic field orientation.…”
Section: Selected Examples Of Astrophysical Applicationssupporting
confidence: 68%
“…Over scales larger than the damping scales, neutrals are strongly coupled with ions and magnetic fields, and thus the turbulence properties measured in neutrals can also reflect the properties of turbulent magnetic fields. As expected, in the diffuse magnetized ISM, the H I gas distribution exhibits turbulence anisotropy (e.g., Kalberla and Kerp 2016), and both the velocity gradient (González-Casanova and Lazarian 2017, Yuen and Lazarian 2017a, 2017b) and density structure (Clark et al 2015) of H I gas are found to well trace the magnetic field orientation.…”
Section: Selected Examples Of Astrophysical Applicationssupporting
confidence: 68%
“…In this work, we studied the effect of anisotropic structures in H i in the isotropic power spectrum using a particular model for the anisotropic power spectrum. Kalberla & Kerp (2016) and Kalberla et al (2017) measure a maximum power anisotropy of a few times 10, which translate to a factor of ∼ 0.5 for the quantity R. This suggests that in presence of anisotropic structures in H i , an estimation of only isotropic power results in an additional degeneracy in the amplitude of the measured optical depth autocorrelation. This degeneracy, however, can be lifted by probing the statistical nature of anisotropic structures.…”
Section: Discussionmentioning
confidence: 95%
“…In this work we are interested in cold neutral medium structures at length scales ranging sub parsecs to a few tens of parsecs. Recent works by Martin et al (2015); Kalberla & Kerp (2016); Kalberla et al (2017); Blagrave et al (2017) and Clark et al (2019) find the existence of anisotropic structures at scales of a few pcs to 100s of pcs in certain directions in the Galaxy with significant alignments along the magnetic field lines. Here, we restrict ourselves to the isotropic estimators of the two point correlation function and hence Ξ depends only on U = | U |.…”
Section: Measuring the Optical Depth Autocorrelation From Radio Intermentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of field aligned HI fibers in the cold neutral medium (Stanimirovic & Zweibel 2018) have been discovered in the diffuse ISM (Clark, Peek & Putman 2014). These linear features vary in scale up to a maximum length ∼ 10 4 AU and are aligned along the poloidal magnetic field lines (Kalberla & Kerp 2016). If the HI fibers can act as refractive lenses, they are most similar to the poloidal magnetic filament model (Gwinn 2019).…”
Section: Filaments With Poloidal Magnetic Fieldsmentioning
confidence: 98%